Factors Affecting Readiness for Self-Care of the Elderly in Nakhon Pathom Province - Rittiboonchai, Witit; Tesmuang, Rawisuda; U- Thairatana, Pichaya; Samlan, Kancharod; Phoorahong, Tanaporn (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The purposes of this research are to 1. Compare the readiness in self-care of the elderly in Nakhon Pathom province classified by personal factors and 2. Study factors affecting the self-care readiness of the elderly people in Nakhon Pathom Province. Researchers collected samples from 400 elderly people selected by Quota data collection in portion of the neighborhood of 7 districts in Nakhon Pathom. The statistics used in data analysis consisted of percentage, mean, standard deviation, t-test, one-way analysis of variance and multiple regression analysis. The research results showed that: 1.The availability of taking care of the elderly in Nakhon Pathom was differences when classified by occupation and having underlying disease statistically significant. 2. Factors affecting the readiness of self-care of the elderly in Nakhon Pathom province are raising awareness of their own health care, health care behaviors of the elderly and knowledge in taking care of one's own health. The multiple regression analysis equation is: Self-care readiness of the elderly (Y) = 1.44 + 0.16. Raising self-care awareness (X1) ** + 0.22 Health care behaviors of the elderly (X2) ** + 0. 21 knowledge of taking care of one's own health (X3) ** With the prediction accuracy of the said equation at 45 percent.